Enabling cognitive radio experimental research - Lotze, Jӧrg (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2011)
Cognitive radio technology is a promising solution for addressing the increasing demand in reliability, connectivity, bandwidth, and quality of future wireless communication systems. This is achieved through continuously and intelligently adapting the radio's operating parameters to current conditions and learning from the past. However, there are many open research questions in this area. Experimental research will play an important role if these questions are to be answered in a manner that convinces the sceptics of the potential of cognitive radio technology.
Keywords: Electronic & Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin.